The effect of amyloid beta on microglia in the aged compared to the young rat brain and the potential exacerbation of ageing in response to abeta infusion - White-Gibson, Ailbhe (Trinity Student Medical Journal, 2012)
Alzheimer’s is an irreversible progressive disease that slowly destroys memory and cognitive skills. The decline in mental fitness associated with this disease is long established. Recent studies have shown it to involve the activation of microglia due to their interaction with Aβ plaques, as a component of the neural inflammatory response which characterises this neurological disease. It was postulated the exacerbating effects of both age and Aβ infusion, separately as well as combined, in this study. An increase in microglial activation was reported in the aged rat brain and in the brains of young rats chronically infused with Aβ infusion. However it was found that Aβ infusion in the aged brain attenuated the activation. This is in stark contrast to previous studies in this area and brings into question the relevance of Aβ infusion in the aged rat brain as a model of AD. However my study confirms the importance of age as a factor in the progression of this debilitating disease.